2006
DOI: 10.1080/15391523.2006.10782467
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Teachers’ Technology Use on Instructional Practices

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 9 publications
3
68
0
4
Order By: Relevance
“…More importantly, with regards ICTs in education, it has been argued that the advent of computers and advanced information and communication technology calls for modification of students" and teachers" roles as it triggers a shift from teacher-centered to constructivist modes of classroom instruction ( [18]; [19]), and causes teachers to confront their established beliefs about instruction ( [20]). Thus, as educational innovations change the modes of school instruction in developed economies, this is also felt in developing economies (Zimbabwe included) of the world.…”
Section: Selected Forms Of Projected Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, with regards ICTs in education, it has been argued that the advent of computers and advanced information and communication technology calls for modification of students" and teachers" roles as it triggers a shift from teacher-centered to constructivist modes of classroom instruction ( [18]; [19]), and causes teachers to confront their established beliefs about instruction ( [20]). Thus, as educational innovations change the modes of school instruction in developed economies, this is also felt in developing economies (Zimbabwe included) of the world.…”
Section: Selected Forms Of Projected Mediamentioning
confidence: 99%
“…The amount of school subjects taught, the number of students in class, time constrain during planning, and the weekly teaching load has been cited as a major factor influencing much of what teachers do in their classrooms ( [28]; [29]; [30]; [20]). Moore, et al [28] reported that teachers resent assignments requiring them to teach subjects they do not know; entail considerable time for class preparations; or teaching very large classes.…”
Section: Workloadmentioning
confidence: 99%
“…The more teachers learn about computers, the more seminars they participate in that deal with specific subjects connected to teaching, the better they will be able to integrate the computer into their teaching methods (Hebenstreit, 1985;Rakes, Fields, & Cox, 2006;Yaghi, 1996). Training courses for teachers should emphasize the essential change in the teachers' role from conventional teaching methods to computer-oriented teaching methods (Hatfield, 1992;Morris, 1992;Steen & Taylor, 1993).…”
Section: Training Of Teachersmentioning
confidence: 99%
“…Additionally, technology adoption was found to be a strong predictor of constructivist teaching. These findings are especially significant since they cite the benefits of technology adoption on higher cognitive skill and development of complex thinking (Rakes, Fields, & Cox, 2006 (Panda & Mishra, 2007). Lowther, Inan, Strahl, and Ross (2008) examined the impact of removing barriers to technology use on the integration of it in instruction.…”
Section: Personal Usementioning
confidence: 99%
“…With an emphasis on constructivist teaching, Rakes, Fields, and Cox (2006) examined the impact of personal technology use on teaching. They found low uses of instructional technologies were caused by lack of time with the tools.…”
Section: Personal Usementioning
confidence: 99%